Netflix, Inc. : risks of a new business model - Allen, Douglas; Vicente, John; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
After ten years of meteoric rises in revenue and subscription customers, a series of communication blunders has put Netflix in a perilous position. Netflix has mishandled key communications regarding account and fee changes affecting its customers. In three months, Netflix has since seen its company's stock price plummet more than 60 percent.
Originally published in Allen, D., Vicente, J., & ORourke, J. S. (2012). Netflix, Inc.: Risks of a new business model. 12-08. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Netflix, Inc; Streaming video; Business losses